PEMBERDAYAAN REMAJA UNTUK MENCEGAH NARKOLEMA - Siswanto, S. (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Background:The prevalence of accessing pornographic material in adolescents tends to increase.. Users of pornography can become addicted to the same internal chemicals made by drugs or drugs called by narkolema.The picture of the incidence of narcolema in SMKN 7 Surakarta known sebannyak 98 students (89.1%) have narcolema Narkolema can cause impaired brain function in the pre frontal cortex or forebrain. The target of this activity is to increase the knowledge of narcolema and can reduce the number of incidents of narcolema. The expected outcomes with the activities of empowerment of adolescents with the provision of material about the dangers of narcolema, 100% of students who follow this activity so that knowledge about narcolema can be absorbed so as to Reduce the incidence of narcolema in adolescents.The methods undertaken in the implementation of this activity is video playback about the dangers of narcolema and its prevention, Discussion, Giving of leaflets. The results of this dedication is in the form of increasing knowledge on students of SMKN 7 Surakarta. The conclusion of the knowledge about danger and the prevention of narcolema followed by 238 participants, to further need to make extension planning accompanied by continuous facilitation by involving participant